Nereididae (Annelida: Polychaeta) from intertidal habitats in the Gulf of Oman, Iran - Yousefi, Shetav; Rahimian, Hasan; Nabavi, Seid Mohammad Bagher; Glasby, Christopher (Zootaxa, 2011)
The species composition and distribution patterns of Nereididae (Annelida: Polychaeta) from the north coast of Gulf of Oman were investigated. Specimens were collected from ten intertidal sites along the Iranian coast, including mangrove, muddy, boulder and rocky, coral and sandy-rocky shore habitats. Eight species of Nereididae were identified: Leonnates decipiens Fauvel, Nereis coutieri Gravier, Neanthes deplanata Mohammad, Perinereis nuntia (Savigny), Perinereis heterodonta Gravier, Perinereis cultrifera (Grube), Perinereis horsti Gravier and Pseudonereis trimaculata Horst. The eight species are redescribed and two Perinereis species, P. heterodonta and P. horsti, currently junior synonyms of P. nuntia and P. vancaurica (Ehlers) respectively, are raised from synonymy. All reported species are new records for the Gulf of Oman, bringing the known total number of species in the family to twelve; P. trimaculata is also a new record for the Arabian Sea–Arabian Gulf region. Nereidid diversity within the region is comparable to other Indo-Pacific coastal regions, and higher than other parts of the world.